The weed vegetation of the bean “Fagiolo Cannellino di Atina” and the red pepper “Peperone di Pontecorvo” PDO crops (Latium, central Italy) - Marta Latini; Emanuele Fanfarillo; Elisa De Luca; Mauro Iberite; Giovanna Abbate (Plant Sociology, 2020)
The weed vegetation of the bean “Fagiolo Cannellino di Atina” (Phaseolus vulgaris L.) and the red pepper “Peperone di Pontecorvo” (Capsicum annuum L.) PDO (Protected Designation of Origin) crops was surveyed by means of 16 relevés, sampled in four farms of southern Latium during July 2019. The relevés were subjected to multivariate analysis, which revealed that the two crops are weeded by vegetation types referable to two different subassociations of Panico-Polygonetum persicariae (Spergulo-Erodion, Eragrostietalia, Digitario-Eragrostietea). Namely, communities colonizing bean fields, which are more mesophilous and richer in Eurasian taxa, are ascribable to the subassociation sorghetosum halepensis. Communities colonizing red pepper fields, which are more thermophilous and richer in Mediterranean taxa, are ascribable to the subassociation cyperetosum rotundi. Floristic, structural, and chorological features of the communities are discussed in relation to environmental factors and agricultural management.